Lasalocida sódica para bovinos de corte em pastejo no período das águas - Almeida, Chafic Mustafé de (2016)
This study aimed to evaluate the effect of sodium Lasalocid inclusion in feeding cattle grazing in the rainy season and supplemented with different nutritional levels during the rainy season, on intake, digestibility and ruminal parameters. We used eight cannulated Nellore rumen weighing about 580 kg, distributed an animal in each paddock, totaling eight pickets in one hectare each formed of Brachiaria brizantha cv. Marandú. The experiment was structured in Latin square design, duplicate 2 (4x4) in a factorial scheme (2x2), with a duration of 112 days divided into 28 days for trial. Treatments were concentrated supplement, mineral supplement and with and without the inclusion of lasalocid. Was provided 0.100 kg per animal day mineral supplement to concentrated supplement was 1% BW, both assuming consumption of 200 mg / head / day of lasalocid. In estimating consumption there was no interaction (P>0.10) on the effects of the supplement and additive, more significant differences (P<0.10) between the concentrated supplement and mineral supplement. There was no interaction (P>0.10) in the apparent digestibility of the supplement and additive, more significant differences (P<0.10) between the supplements. In the estimation of ruminal pH was no interaction (P<0.10) according to the schedule and supplement. There were differences (P<0.10) between supplement. In the estimation of ammonia nitrogen was no interaction (P<0.10) in time function and supplement, however there was no difference (P>0.10) in the concentration of ruminal nitrogen between with and without inclusion of lasalocid. In estimating the VFA no interaction (P>0.10) between the effects of the supplement, additive and time.The use of lasalocid in finishing beef cattle has a positive effect on consumption of animals because they have not reduced, but adversely affects the digestibility for not presented improvements with the use of lasalocid. However the lasalocid does not alter the production of volatile fatty acids and concentration of ruminal ammonia nitrogen, most maintain rumen pH. With this, it is suggested more studies on these effects of lasalocid through the parameters evaluated in this study, using different dosages of lasalocid in supplementation of beef cattle in the finishing phase.